Flaxseed Consumption May Reduce Blood Pressure: A Systematic Review and Meta-Analysis of Controlled Trials. Issue 4 (4th March 2015) - Khalesi, Saman; Irwin, Christopher; Schubert, Matt
Abstract: Background: High blood pressure is a major health burden positively associated with the risk of cardiovascular disease and other chronic diseases. Flaxseed is a rich dietary source of α-linolenic acid, lignans, and fiber, with a number of positive health benefits on blood pressure. Objective: The purpose of this study was to clarify the effect of flaxseed consumption on blood pressure. Further, the influence of baseline blood pressure, type of flaxseed supplementation, and duration of flaxseed supplementation on blood pressure was explored. Method: PubMed (MEDLINE), Cumulative Index to Nursing and Allied Health Literature, and Cochrane Library (Central) were searched through July 2014 for studies in which humans supplemented their habitual diet with flaxseed or its extracts (i.e., oil, lignans, fiber) for ≥2 wk. Results: A total of 11 studies (14 trials) were included in the analysis. Random-effects meta-analyses were conducted for the mean difference in blood pressure. Results indicated that flaxseed supplementation reduced systolic blood pressure (−1.77 mm Hg; 95% CI: −3.45, −0.09 mm Hg; P = 0.04) and diastolic blood pressure (−1.58 mm Hg; 95% CI: −2.64, −0.52 mm Hg; P = 0.003). These results were not influenced by categorization of participants into higher baseline blood pressure (≥130 mm Hg). An improvement in diastolic blood pressure was observed in subgroup analysis for consuming whole flaxseed (−1.93 mm Hg; 95% CI: −3.65, −0.21 mm Hg; P < 0.05) and duration of consumption ≥12 wk (−2.17 mm Hg; 95% CI: −3.44, −0.89 mm Hg; P < 0.05). Conclusion: The present meta-analysis suggests that consumption of flaxseed may lower blood pressure slightly. The beneficial potential of flaxseed to reduce blood pressure (especially diastolic blood pressure) may be greater when it is consumed as a whole seed and for a duration of >12 wk.